PENGEMBANGAN PARIWISATA HALAL DESA SETANGGOR - Feriyadin Feriyadin; Akhmad Saufi; Baiq Handayani Rinuastuti (Master of Management, Mataram University, 2021)
Setanggor tourism managers make halal tourism as a new innovation in the development of tourist villages. The value of Islamic law as a reference for the development of halal tourism in Setanggor Village. However, in the development of the tourism industry in Setanggor Village, it is inseparable from the challenges, namely the low participation of youth at the planning and decision-making stages to develop tourism, and youth prefer to seek income outside their area because of economic conditions in the village are not yet supported, so local youth are less participating in developing tourism in the environment. This shows that the readiness of human resources (especially youth) in developing halal tourism is still inadequate. The research data were analyzed using a qualitative approach through in-depth interviews, direct observation, and documentation support related to the research objectives. In-depth interviews were conducted with 6 Tourism Managers and 1 Head of Setanggor Village, then the interview data were recorded and continued with analysis using content analysis.The results of this study indicate that the management of the Setanggor tourism village offers a unique travel experience by enjoying natural attractions; arts-cultural attractions; local food attractions; and halal tourist attractions. The tour packages offered as tourism products are local activities, nature, and the unique traditions / culture of the Muslim community in Setanggor tourist destinations as an effort to attract domestic tourists and foreign tourists, both Muslim and non-Muslim. The presence of Halal tourism concept in the development of tourism in Setanggor Village is an effort to foster an entrepreneurial spirit in tourism and cultural preservation of the local community whose activities are inseparable from religious factors, namely Islam.Keywords:Halal Tourism, Tourism Village, Setanggor Village.